2013
DOI: 10.1089/jcr.2013.0015
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine and Substance Use Disorders

Abstract: affeine is the most consumed psychoactive drug in the world. As a psychostimulant, it shows all the pharmacological properties of classical psychostimulants, such as cocaine and amphetamine. Those properties include arousal, motor activation, and reinforcing effects. Nevertheless, those effects are milder for caffeine, which depends on its unique mechanism of action, adenosine receptor antagonism. Classical psychostimulants produce a direct potentiation of central dopaminergic, noradrenergic, and serotoninergi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 7 publications
0
15
1
Order By: Relevance
“…To the extent that caffeine is experienced as increasingly rewarding, the use of substances to regulate mood in general may be reinforced. This mechanism is particularly concerning for youth who are experimenting with new substances, as caffeine use may potentiate the rewarding effects of the new substance and lead to escalation and chronic problems . In that regard, early caffeine consumption could serve to increase the use of nicotine, alcohol and substances in general .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the extent that caffeine is experienced as increasingly rewarding, the use of substances to regulate mood in general may be reinforced. This mechanism is particularly concerning for youth who are experimenting with new substances, as caffeine use may potentiate the rewarding effects of the new substance and lead to escalation and chronic problems . In that regard, early caffeine consumption could serve to increase the use of nicotine, alcohol and substances in general .…”
Section: Discussionmentioning
confidence: 99%
“…Caffeine is a psychostimulant possessing arousal, motor activation and reinforcing properties . Stimulant effects are believed to be a product of the competitive blockade of adenosine receptors both centrally and peripherally .…”
Section: Introductionmentioning
confidence: 99%
“…ED marketing promoting the psychoactive effects of the beverage (Reissig et al, 2009), and iii.) caffeinated ED consumption resulting in 'cross-sensitisation' whereby the dopamine system is primed to respond in a rewarding and reinforcing manner to alcohol and other stimulant drugs (Arria et al, 2014;Ferré, 2013;Temple, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…16 Some potential risk factors, such as technology use, have featured heavily in adolescent sleep research during recent years, 17,18 whereas others, such as caffeine use, have been largely neglected. 19 This is despite caffeine being a substance with psychostimulant properties (and thus contraindicated for sleep), 20 excessive consumption of caffeinated products by adolescents, 21 and rapid growth of a number of high-caffeinated food and beverage products available to, and marketed at, adolescents. 22 A new meta-analysis of risk factors associated with adolescent sleep by the authors' group has shown that use of caffeinated products were linked to less sleep in adolescents, whereas using a phone, the Internet, or TV was not.…”
Section: Introductionmentioning
confidence: 99%